Narrative and Aesthetic Values in Wayang Bocah Arjuna Wiwaha: A Strategy for Interactive Cultural Education - Suparti, Suparti; Lanjari , Restu (Jurnal Seni Tari, 2025)
This study explores the narrative and aesthetic values embedded in the Wayang Bocah performance of Arjuna Wiwaha at Padhepokan Tjipta Boedaja, and examines its function as an interactive cultural education strategy for Generation Z. Employing a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and performance documentation. Findings reveal that the adaptation of the Arjuna Wiwaha story aligns effectively with the values, language, and visual expectations of younger audiences, enhancing both engagement and cultural relevance. Moreover, the incorporation of interactive learning strategies—where children actively participate in the performance—proves instrumental in fostering cultural appreciation and critical reflection. This research contributes to the discourse on arts-based pedagogy by offering a model for integrating traditional performance arts into contemporary educational practices.